IMPLEMENTATION OF PATHFINDING ALGORITHM IN SCOUT EXPLORING GAME WITH DIGITAL GAME-BASED LEARNING-INSTRUCTIONAL DESIGN METHOD - Kurniadi, Dede; Tresnawati, Dewi; Sopiah, Dede (Jurnal Teknik Informatika (Jutif), 2024)
Scouting, or Praja Muda Karana, which means young people who like to work, has become an extracurricular activity that must be held in schools and is regulated by the Law of the Republic of Indonesia. Tri Satya and Dasa Dharma are scouting principles applied through scouting teaching methods, including interactive learning in the open air. One form of implementation is through exploration activities. Along with the rapid development of science and technology, scouting material is now easier to convey through educational games. Educational games are specifically designed to teach specific concepts and understanding, as well as to guide, train skills, and motivate players. Therefore, the aim of making this game is to describe and simulate exploration activities, which is one of the essential aspects of scouting activities. Applying the A* pathfinding algorithm in a 3D game with a scout exploration theme is critical in helping players determine the fastest path to the destination post. This game is expected to improve the player's learning experience with realistic challenges and interactive learning. This game was developed using the Digital Game-Based Learning-Instructional Design (DGBL-ID) method and tested using black box testing. The implementation results show that the scout exploration game application provides positive benefits, as proven by the results of a questionnaire using the Guttman scale with the title "Very Good," indicating that this game is a learning medium that is easy to understand and fun.